2022
DOI: 10.1093/gerona/glac184
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Mass Index on the Risk of Back Pain: Estimating the Impacts of Weight Gain and Loss

Abstract: Background The relationship between obesity and back pain in older populations is poorly understood. This study aimed to examine (1) the impacts of changes in obesity status on back pain risk and (2) the heterogeneity in the influence of changes in obesity status according to muscle strength. Methods We analyzed 6,868 participants in waves 4 (2008–2009), 6 (2012–2013), and 7 (2014–2015) of the English Longitudinal Study of Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Further, the effect of weight gain on comorbidities of motor functions should not be ignored, 44,45 as it leads to comorbidities such as joint diseases, osteoarthritis, and lower back pain. In particular, lower‐extremity mobility such as walking, stair climbing, and chair rise ability, worsens with increasing weight gain in older adults 46,47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the effect of weight gain on comorbidities of motor functions should not be ignored, 44,45 as it leads to comorbidities such as joint diseases, osteoarthritis, and lower back pain. In particular, lower‐extremity mobility such as walking, stair climbing, and chair rise ability, worsens with increasing weight gain in older adults 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…Smoking cessation and increased physical activity not only reduce the risk of future disability but also activate nitric oxide, decrease reactive oxygen species, and reduce the risks of VED and inflammation. 42,43 Further, the effect of weight gain on comorbidities of motor functions should not be ignored, 44,45 as it leads to comorbidities such as joint diseases, osteoarthritis, and lower back pain. In particular, lower-extremity mobility such as walking, stair climbing, and chair rise ability, worsens with increasing weight gain in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The following variables assessed in wave 4 were used as covariates: sex (U.S. Department of Health and Human Services, 2020; Fancourt & Steptoe, 2018), race (U.S. Department of Health and Human Services, 2020; Fancourt & Steptoe, 2018), duration of education (Ikeda et al, 2019, 2021; Ikeda, Matsuyama, Murakami, & Osaka, 2022), age (U.S. Department of Health and Human Services, 2020; Ikeda et al, 2019, 2021), marital status (U.S. Department of Health and Human Services, 2020; Ikeda et al, 2019, 2021), equalized household income (U.S. Department of Health and Human Services, 2020; Ikeda et al, 2019, 2021), weekly engagement in mild, moderate or vigorous physical activity (Chiolero et al, 2008; Ikeda, Cooray, Murakami, & Osaka, 2022), lung disease diagnosis (Thomson, 2004), asthma diagnosis (Thomson, 2004), osteoporosis diagnosis (Glassman et al, 2000), cancer diagnosis (U.S. Department of Health and Human Services, 2020), depressive symptoms (Ikeda et al, 2019; Murphy et al, 2003), handgrip strength (Ikeda, Cooray, Suzuki, et al, 2022; Kojima et al, 2015), body mass index (Dare et al, 2015; Ikeda, Cooray, Suzuki, et al, 2022) and back pain and its intensity. Furthermore, the following time‐varying variables assessed in wave 6 were used as covariates: age; marital status; equalized household income; participation in mild, moderate or vigorous physical activity on a weekly basis; diagnosis of lung disease, asthma, osteoporosis and cancer; depressive symptoms; handgrip strength; body mass index; and back pain and its intensity.…”
Section: Methodsmentioning
confidence: 99%
“…Body mass index was calculated as body weight (kg) divided by the square of height (m), and it was measured by trained nurses. Furthermore, both handgrip strength and body mass index were included in our model because a previous study reported the heterogeneity in the impacts of changes in obesity status on back pain according to muscle strength (Ikeda, Cooray, Suzuki, et al, 2022). We used back pain and its intensity assessed at waves 4 and 6 as covariates for the following reasons.…”
Section: Methodsmentioning
confidence: 99%
“…The longitudinal modified treatment policy (LMTP) approach is a recently developed nonparametric alternative that can be used to define causal research questions and estimate relevant statistical parameters flexibly using observational data. Causal effects are defined by shifting the exposure as a deterministic function of the observed level of exposure (Díaz et al 2021; Ikeda et al 2022; Nugent and Balzer 2023).…”
Section: Introductionmentioning
confidence: 99%